Oxygen transfer in hydrocarbon-aqueous dispersions and its applicability to alkane-based bioprocesses - Correia, Leslie Daniel Camara (Stellenbosch : University of Stellenbosch, 2008)
Thesis (MScEng (Process Engineering))--University of Stellenbosch, 2007.